The Relationship between Cariogenic Food Consumption and Tooth Brushing Habits to Dental Caries in 4th, 5th and 6th Grade Students at SDN 1 Cikulur, Lebak Banten Regency. - Weny Martalinda; Nur Asniati Djaali; Brian Sri Prahastuti (Green Publisher Indonesia, 2026)
Dental caries is one of the most common oral health problems among school-aged children and is often neglected, despite its potential impact on quality of life, academic achievement, and overall health. High consumption of cariogenic foods such as candies, chocolates, sugary drinks, and other sweet snacks, combined with poor and irregular tooth-brushing habits, are the main contributing factors to the occurrence of dental caries in elementary school children. This research analyzed the relationship between cariogenic food consumption and tooth-brushing habits with the incidence of dental caries among 4th–6th graders at SDN 1 Cikulur, Lebak, Banten, and examined the confounding effects of gender, parental education, and socioeconomic status. A cross-sectional design with stratified random sampling was used, involving 76 respondents. Data were collected via questionnaires and visual dental examinations, then analyzed using Chi-Square and Multiple Logistic Regression to assess relationships while controlling for confounders. The findings revealed a significant relationship between cariogenic food consumption and tooth-brushing habits with dental caries. Children with high cariogenic food consumption were seven times more likely to develop caries, while those with poor tooth-brushing habits had an 11.6 times greater risk after adjusting for parental education and socioeconomic status. The study recommends strengthening oral health education in schools, enforcing stricter supervision of children's food consumption through school policies and Puskesmas programs, and increasing family involvement in shaping healthy behaviors. Cross-sectoral collaboration is expected to sustainably reduce the prevalence of dental caries among elementary school children.